The Moderating Role of Parental Warmth on the Relation Between Verbal Punishment and Child Problem Behaviors for Same-sex and Cross-sex Parent-Child Groups - Anonas, Maria Roberta L (Archīum Ateneo, 2015)
This study investigates the relation between parental verbal punishment and externalizing and internalizing behavior problems in Filipino children, and the moderating role of parental warmth in this relation, for same-sex (mothers-girls; fathers-boys) and cross-sex parent-child groups (mothers-boys; fathers-girls). Measures used were the Rohner Parental Acceptance-Rejection and Control Scale (PARQ/Control), the Achenbach Child Behavior Checklist (CBC), and a discipline measure (DI) constructed for the study. Participants were 117 mothers and 98 fathers of 61 boys and 59 girls who responded to a discipline interview, the Parental Acceptance-Rejection and Control scale (PARQ/Control) and the Achenbach Child Behavior Checklist via oral interviews. Hierarchical multiple regression analyses (with Bonferroni-corrected alpha levels) revealed that maternal frequency of verbal punishment was positively related to internalizing and externalizing outcomes in boys and girls whereas paternal frequency of verbal punishment was positively related to girls’ externalizing behavior. Significant interactions between verbal punishment and maternal warmth in mother-girl groups were also found for both internalizing and externalizing behaviors. While higher maternal warmth ameliorated the impact of low verbal punishment on girls’ internalizing and externalizing behaviors, it exacerbated the effect of high verbal punishment on negative outcomes.